Sida cordifolia is efficacious in models of Huntington’s disease by reducing ER stress - Simha, Prasanna K.; Mukherjee, Chandramouli; Kumar Gupta, Vikas; Bhatia, Karishma; Nagar, Padmanabhi; ZA, Azeem Nazeer; Godbole, Ashwini; Sahu, Bhavani Shankar; Upadhyay, Sanjeev K. (Frontiers in Molecular Biosciences, 2025)
Neurodegenerative disorders (NDs) are a major class of diseases where modern science has not succeeded in providing solutions to the desired levels. ER stress pathway is implicated in pathophysiology of several neurodegenerative disorders, especially those classified as proteinopathies. Several traditional medicines are used to treat neurodegeneration and Sida cordifolia (SC) is one of the common ingredients in formulations used for treating NDs and neuropathic pain. However, the mode of action is not clear. We studied the effectiveness of SC in Huntington’s Disease (HD) model using Caenorhabditis elegans and mammalian cells. We used a transgenic C. elegans that expresses mutant huntingtin protein tagged with Yellow Fluorescent Protein (YFP) in their body wall muscle. In C. elegans, SC not only improved motility but also substantially increased the life span. Cell-based studies using inducible mutant Huntingtin protein (mHTT) with a long polyQ tail tagged with EGFP showed that SC profoundly modulates ER stress, reducing the stress caused by mHTT protein. The study showed that the mode of action of SC, at least partially, is through modulation of ER stress pathway, thereby normalizing the changes brought about by overexpression of mHTT.